2005
DOI: 10.1021/ic051166+
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of Dithiophosphates in the Syntheses of Copper(I) Complexes with Bis(diphenylphosphino)alkanes: Abstraction of Chloride from Dichloromethane

Abstract: Reactions of [Cu(CH(3)CN)(4)]X (X = PF(6), BF(4)) with bis(diphenylphosphino)methane (dppm = Ph(2)PCH(2)PPh(2)) and ammonium dialkyldithiophosphates, (NH(4))[S(2)P(OR)(2)] (R = Et, (i)Pr), yield a series of novel Cu(I) polynuclear complexes, trinuclear [Cu(3)(mu-dppm)(3)(mu(3)-Cl){S(2)P(OEt)(2)}] (PF(6)) 1 and [Cu(3)(mu-dppm)(2){S(2)P(OR)(2)}(2)](PF(6)) (R = Et, 2; (i)Pr, 3), tetranuclear [Cu(4)(mu-dppm)(2) {S(2)P(OEt)(2)}(4)] 4, and hexanuclear [Cu(6)(mu-dppm)(2)(mu(4)-Cl){S(2)P(O(i)()Pr)(2)}(4)](BF(4)) 5. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Current synthetic efforts in the field concentrate on metal complexes with ligands designed by formally replacing O atoms in phosphate ions with OR, SR, S, Se, OSe and combinations thereof, and ultimately on the construction of larger molecular aggregates. [15][16][17][18][19][20] In previous work, it was shown that reactions of metal salts MX (X = alkoxide, thiolate, carboxylate) with Lawessons reagent (L.R.) [{RP(S)A C H T U N G T R E N N U N G (m-S)} 2 ] (R = 4-anisyl) [21] or the analogous Se compound Woollins reagent (W.R.) [{PhP(Se)A C H T U N G T R E N N U N G (m-Se)} 2 ] [8,22] offer an alternative route to complexes containing P/S-or P/Se-based anionic ligands.…”
Section: Pe [Rp(e)a C H T U N G T R E N N U N G (Esime 3 ) 2 ] [{Rpmentioning
confidence: 99%
“…Current synthetic efforts in the field concentrate on metal complexes with ligands designed by formally replacing O atoms in phosphate ions with OR, SR, S, Se, OSe and combinations thereof, and ultimately on the construction of larger molecular aggregates. [15][16][17][18][19][20] In previous work, it was shown that reactions of metal salts MX (X = alkoxide, thiolate, carboxylate) with Lawessons reagent (L.R.) [{RP(S)A C H T U N G T R E N N U N G (m-S)} 2 ] (R = 4-anisyl) [21] or the analogous Se compound Woollins reagent (W.R.) [{PhP(Se)A C H T U N G T R E N N U N G (m-Se)} 2 ] [8,22] offer an alternative route to complexes containing P/S-or P/Se-based anionic ligands.…”
Section: Pe [Rp(e)a C H T U N G T R E N N U N G (Esime 3 ) 2 ] [{Rpmentioning
confidence: 99%
“…The main objective is to produce new functional materials with specific molecular arrangements capable of showing the desirable properties [16,17]. With flexible ligands, the competition between chelating and bridging coordination modes is an important factor in producing mono, di, and polynuclear metal complexes [18][19][20][21]. We have recently studied the coordination behavior of several Schiff-base ligands such as ca 2 en, Phca 2 en, Phca 2 dab, ca 2 dapte and (thio) 2 dapte [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in chain length of diphosphine from -(CH 2 ) 2 -in dppe to -(CH 2 ) 4 -in dppb, produces two types of polymers depending on the molar ratio used; a zigzag chain, 7 (Fig. 5), in which dppb bridges two Ag(dtp) units having a similar bonding pattern that observed in dppe polymer 5a, 5a 0 and [Cu(dppe){S 2 P(OR) 2 }] 1 [30], and the other zigzag chain 8 in which the dppb ligands bridge dimeric Ag 2 (dtp) 2 units (Fig. 6).…”
Section: Structure Of Polymers 5-8mentioning
confidence: 93%
“…Calc. for C 30 The method is the same as for 1, except using dichloromethane as solvent with [Ag 2 (dppb) 2 …”
Section: Materials and Instrumentsmentioning
confidence: 99%